Recreating Virginity in Iran: Hymenoplasty as a Form of Resistance. (14th March 2016) - Ahmadi, Azal
Abstract : Hymenoplasty is a controversial surgery in Iran, where a woman's failure to present herself as virginal for marriage may result in severe social repercussions. Critical literature surrounding this clandestine surgery is sparse. During ethnographic fieldwork in Tehran, I interviewed women who have and have not undergone hymenoplasty and physicians who perform it. Using a Foucauldian framework, I argue that the medicalization of virginity is a form of female social control in Iran. The resulting narratives and discourses suggest that hymenoplasty is a covert form of resistance against socioculturally prescribed sexual inegalitarianism that restricts women to the social sphere of premarital chastity. By manipulating the medicalization of virginity, women inadvertently resist dichotomous gendered classifications that constrain them as either the deviant woman who has premarital sex or the normal woman who remains virginal until marriage. These women deviate from a fixed notion of gender embodiment, eroding socioculturally constituted categorical boundary markers regarding femininity.